1996
DOI: 10.1159/000150471
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the Large Hepatitis B Virus Surface Protein in Viral Particle Morphogenesis

Abstract: The hepatitis B virus (HBV) envelope and the subviral lipoprotein particles contain three viral surface proteins (L, M, and S) which are expressed from one open reading frame by the usage of three start codons and a common stop codon. The largest surface protein L has some unusual properties. It adopts two different transmembrane topologies due to a posttranslational switch of the folding in approximately half of the L proteins. L molecules which expose their N-terminal preSl domain on the viral particle surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 17 publications
0
39
0
4
Order By: Relevance
“…In vitro studies suggest that M protein is not essential for in vitro HBV replication (18), virion morphogenesis (19), or infectivity (20). Furthermore, because an M protein-deficient mutant can be found in patients with fulminant hepatitis, it was suggested that M protein is not required for in vivo viral replication (21).…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 99%
See 3 more Smart Citations
“…In vitro studies suggest that M protein is not essential for in vitro HBV replication (18), virion morphogenesis (19), or infectivity (20). Furthermore, because an M protein-deficient mutant can be found in patients with fulminant hepatitis, it was suggested that M protein is not required for in vivo viral replication (21).…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 99%
“…The NotI site (underlined) is preceded by six random nucleotides and followed by an HBV sequence (nt 3188ϳ3207). The reverse primer used was (N) 6 GCGGCCGCTTA(X) 19 , where N and X represent random nucleotides and a bracketed HBV sequence, respectively. The NotI site (underlined) is followed by the stop codon (TTA).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Virion morphogenesis starts with encapsidation by the capsid, or core, protein of a complex consisting of one of the viral RNAs, the reverse transcriptase, and probably cellular chaperones [5]. After reverse transcription, the DNA-containing nucleocapsid buds into a pre-Golgi compartment, exiting from the cell as enveloped virion [6].…”
Section: Introductionmentioning
confidence: 99%